Experimental Response of Reinforced Concrete Frames With AAC Masonry Infill Walls to In-plane Cyclic Loading. (August 2015) - Schwarz, S.; Hanaor, A.; Yankelevsky, D.Z.
Abstract: The paper presents an experimental investigation to assess some aspects of the influence of non-structural masonry infill walls on seismic resistance of RC frames. Low cycle horizontal loading of nine half-scale specimens, employing autoclave-cured aerated concrete (AAC) blocks as infill, is designed to test the influence of four parameters. The main effects indicated by the results are: The overall influence of the masonry infill walls, as compared with frames without infill walls, is some 200% increase in the yield load (the capacity) and close to 60% decrease in ductility. While the influence of the aspect ratio (height/width) on capacity appears to be small, narrow panels (high aspect ratio) have substantially higher ductility. The influence of the infill wall's construction method is a mild increase in capacity and a slight reduction in ductility of integral wall (built before frame casting) as compared to non-integral wall (built following frame casting) construction. Vertical prestress of the masonry wall panel has a large positive effect on both, capacity and ductility of integral infill panels. While the method of prestress applied does not represent adequately the effect of gravity loads, it could serve as a potential method for seismic upgrade. Openings in masonry infill walls produce capacity and ductility values that are intermediate between those of the frame with full infill wall and the frame without infill.